2010
DOI: 10.2174/1874331501004010049
|View full text |Cite
|
Sign up to set email alerts
|

Potential Greenhouse Gas Mitigation through Temperate Tree-Based Intercropping Systems

Abstract: Increasing awareness of global climate change has pressured agricultural producers to reduce greenhouse gas (GHG) emissions while at the same time encouraging them to maintain food production needed for an increasing population. Tree-based intercropping (TBI) systems are believed to be useful in climate change mitigation, especially in temperate regions, due to their potential to reduce GHG emissions from agricultural practices. The purpose of this paper is therefore to review some of the research conducted on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…For instance, the higher content of mineral nitrogen and soil moisture favour denitrification, which was manifested as elevated values of potential denitrification in our measurements. In our field site, soil moisture was nearly 40 %, corresponding to 80 % WFPS, which is suitable for earthworm N 2 O contribution (Evers et al, 2010). Another potential mechanism for increased N 2 O emissions in the field are the burrows that may act as large pores that ease the diffusion of N 2 O from the bottom soil and allow more of the N 2 O ending up in the atmosphere without being reduced to N 2 .…”
Section: Discussionmentioning
confidence: 98%
“…For instance, the higher content of mineral nitrogen and soil moisture favour denitrification, which was manifested as elevated values of potential denitrification in our measurements. In our field site, soil moisture was nearly 40 %, corresponding to 80 % WFPS, which is suitable for earthworm N 2 O contribution (Evers et al, 2010). Another potential mechanism for increased N 2 O emissions in the field are the burrows that may act as large pores that ease the diffusion of N 2 O from the bottom soil and allow more of the N 2 O ending up in the atmosphere without being reduced to N 2 .…”
Section: Discussionmentioning
confidence: 98%
“…Few studies have evaluated greenhouse gas emissions from the intercropping of woody and perennial grasses such as switchgrass. Evers et al (2010) reported mean N 2 O emission from monoculture and tree-based intercropping were 10.7 and 7.5 g ha -1 d -1 , respectively.…”
mentioning
confidence: 95%
“…These systems commonly include tree or other woody species often from tropical or semi-tropical environments within agroforestry production systems (Suresh and Rao, 1999;Nissen et al, 2001;Prasad et al, 2010), combined with annual food crops grown using low inputs (Gliessman, 2007;Lithourgidis et al, 2011;Gebru, 2015). Few studies of intercropping woody species with annual food crops in North America have been conducted (Thevathasan and Gordon, 2004;Rivest et al, 2009;Evers et al, 2010). Thevathasan and Gordon (2004) summarized 15 yr of intercropping research with ten tree species and four annual grain crops.…”
mentioning
confidence: 99%
See 2 more Smart Citations